The Influence of Online Learning Competency, Adaptability And Lecturer's Job Satisfaction on The Performance of Politeknik Negeri Medan Lecturer - Evi Linda (Journal Of Management Analytical and Solution (JoMAS), 2022)
Restrictions  on  physical  contact  during  the  COVID-19  pandemic  have  resulted  in  the government implementing a work from home (WFH) program. Education is one of the areas affected by the Covid-19 pandemic. As a result of these changes, universities must change the performance of lecturers in carrying out the Tri Dharma of higher education. Lecturer performance is one of the determining factors for the success of the teaching and learning process in universities. It can be said that if the lecturer's performance is good, the university's performance will also be good. The purpose of this study was to determine and analyze the effect of online learning competence, adaptability and job satisfaction on the performance of lecturers at the Politeknik Negeri Medan. The research method used is a quantitative method. The place of this research was carried out at the Politeknik Negeri Medan, North Sumatra. The population in this study were all permanent lecturers at the Medan State Polytechnic, amounting to 338 people, where to determine the sample, the researchers used the Slovin formula to obtain 78 people. Data obtained through primary data and secondary data. The results of the study at the significance level of = 5% (0.05) showed that through the results of the t-test it was proven that online learning competence, adaptability and job satisfaction had a positive and significant effect on the performance of Politeknik Negeri Medan lecturers. The F-test results show that online learning competence, adaptability and job satisfaction simultaneously have a significant effect on the performance of lecturers at the Politeknik Negeri Medan. And from the results of this study,